2014
DOI: 10.1111/jace.12980
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Processes During Energy‐Saving Preparation of Lightweight Ceramics

Abstract: Lightweight glass‐ceramic material similar to foam glass was obtained at 700°C–800°C directly from alkali‐activated silica clay and zeolitized tuff without preliminary glass preparation. It was characterized by low bulk density of 100–250 kg/m3 and high pore size homogeneity. Chemical processes occurring in alkali‐activated silica clay and zeolitized tuff were studied using X‐ray diffraction, thermal gravimetry, IR‐spectroscopy, and scanning electron microscopy. Pore formation in both compositions is caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
2
9
0
1
Order By: Relevance
“…The similar dependence of resulting porosity on the fineness of grinded raw material was observed earlier for alkali‐activated dense zeolite‐rich rocks with cryptocrystalline zeolitization . These studies have shown that NaOH serves not as a flux only, but also reacts with zeolites giving additional pore‐forming gas source (hydrated sodium polysilicates).…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…The similar dependence of resulting porosity on the fineness of grinded raw material was observed earlier for alkali‐activated dense zeolite‐rich rocks with cryptocrystalline zeolitization . These studies have shown that NaOH serves not as a flux only, but also reacts with zeolites giving additional pore‐forming gas source (hydrated sodium polysilicates).…”
Section: Resultssupporting
confidence: 76%
“…It was reported that interaction of OCT‐phase with NaOH solution results in the formation of hydrated sodium polysilicates, Na 2 O· m SiO 2 · n H 2 O (liquid glass)—an important source of pore‐forming gas (water vapor). The presence of latter can be identified from amorphous halo on XRD profiles and on DTG maxima near 250°C and 350°C . Our XRD studies, however, have shown that amount of amorphous constituent after interaction of raw material with NaOH does not depend on the powder fineness (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations